METHODOLOGICAL FEATURES OF USING THE ELECTRONIC LINGUOMETHODOLOGICAL TOOLS IN FUTURE PRIMARY SCHOOL TEACHER PROFESSIONAL TRAINING - Khyzhniak, Inna; Ishutina, Olena (Професіоналізм педагога: теоретичні й методичні аспекти, 2019)
The article is devoted to the relevant issues of electronic linguomethodology, which is an innovative methodological branch of science that has started its active development in the mid-twentieth century within the linguistic and pedagogical sciences, exploring the theoretical and practical aspects of the use of electronic tools in language learning and teaching methods, prompting the laws of creation and application of these tools in the learning process, summarizing the typical shortcomings and suggesting ways to prevent and solve them. The purpose of the article is to analyse the leading methodological features that reflect the changes that should be made by the use of electronic linguomethodological tools in the professional training of a future primary school teacher. The authors emphasize that the modern professional linguomethodological training requires the introduction of the content module “Means of Electronic Linguomethodology for Primary School” for undergraduate students and the discipline “Electronic Linguomethodology for HEI” for Master students; integration of the courses in methodological and basic disciplines; creation of distance learning courses, electronic textbooks and manuals on linguomethogology to enhance the learning process visualization. The role of students’ independent and self-activities with the use of electronic linguomethodiological tools, which develop teaching and research qualities of future primary school teachers, is emphasized. Different classifications of teaching methods of language and linguomethodological disciplines are analysed and the optimal ones are determined. According to the authors, for teaching linguomethodology, it is advisable to apply a classification that includes both traditional methods (lecture, problem, research, discussion) and innovative, in particular, interactive, project, as well as e-learning methods. It is noted that the use of distance learning elements in teaching linguomethodology should be a system, in which self-study dominates, but “one to one”, “one to many”, “many to many” methods are also important.